SIMULTANEOUS SEISMIC INVERSION AND SEISMIC ATTRIBUTE APPLICATION FOR FACIES AND RESERVOIR CHARACTERIZATION IN THE MENTAWA - MINAHAKI FORMATION, BAHAMA AREA, BANGGAI BASIN - Atalla Putra, Daffa
The Banggai Basin, formed by the collision between the Eastern Arm of Sulawesi and the Banggai-Sula Microcontinent during the Miocene, is one of Indonesia's productive hydrocarbon basins with the Mentawa Formation, which has been proven to be a gas reservoir. This reservoir consists of carbonate reef build-ups in the platform margin zone that have undergone meteoric vadose diagenesis, increasing porosity and hydrocarbon storage potential. To understand the characteristics of the Mentawa gas reservoir, data from four main wells DNG-2, WOL-1, WOL-2, and EWO-1, which have Mentawa well markers were used along with 3D Pre-stack seismic data in the time domain for inversion input, and 3D post-stack seismic data in the depth domain for horizon and fault interpretation. RMS and interval velocity models were also used for depth-time conversion and vice versa. Sensitivity analysis of rock physical parameters was necessary before applying simultaneous seismic inversion to identify parameters sensitive to hydrocarbon presence, such as p-impedance, density, and lambda-rho. The target reservoir interpretation was then conducted using seismic attributes such as envelope and cosine of phase to identify horizons, fault structures, and facies. Following this, simultaneous seismic inversion was applied using partial angle stack seismic data derived from pre-stack angle gather seismic data, which contains angle information, allowing the use of Aki-Richards equations to model reflectivity as a function of angle. This enables the simultaneous seismic inversion to utilize the amplitude response variations based on angle to generate representative parameters of subsurface conditions, producing volumes of physical properties such as P-impedance, S-impedance, and density. The resulting P-impedance volume was then used to create a porosity volume and lambda-rho volume. The results of the simultaneous seismic inversion can produce a representative map of hydrocarbon distribution, showing gas accumulation in the reef build-up with high porosity which was influenced by relative sea-level changes, and revealing the relationship between porosity and fault structures in the study area.